2011
DOI: 10.1007/s00122-011-1662-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, structure, gene flow and evolutionary relationships within the Sorghum bicolor wild–weedy–crop complex in a western African region

Abstract: Gene flow between domesticated plants and their wild relatives is one of the major evolutionary processes acting to shape their structure of genetic diversity. Earlier literature, in the 1970s, reported on the interfertility and the sympatry of wild, weedy and cultivated sorghum belonging to the species Sorghum bicolor in most regions of sub-Saharan Africa. However, only a few recent surveys have addressed the geographical and ecological distribution of sorghum wild relatives and their genetic structure. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
57
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 51 publications
11
57
0
7
Order By: Relevance
“…and with the SSRs markers. Nonetheless, our results are similar to that of Sagnard et al (2011) (7.48 alleles in average per locus) who worked on 455 sorghum accessions from Mali and Guinea using 15 SSR markers. However, the average number calculated in the present study was lower than that reported by Deu et al (2008) and Bhosale et al (2011), which were 10.43 and 19, respectively from 472 accessions of sorghum from Niger and 219 accessions of sorghum cultivated in West Africa and assessed by means of 28 and 27 SSR markers, respectively.…”
Section: Overall Genetic Diversitysupporting
confidence: 87%
See 1 more Smart Citation
“…and with the SSRs markers. Nonetheless, our results are similar to that of Sagnard et al (2011) (7.48 alleles in average per locus) who worked on 455 sorghum accessions from Mali and Guinea using 15 SSR markers. However, the average number calculated in the present study was lower than that reported by Deu et al (2008) and Bhosale et al (2011), which were 10.43 and 19, respectively from 472 accessions of sorghum from Niger and 219 accessions of sorghum cultivated in West Africa and assessed by means of 28 and 27 SSR markers, respectively.…”
Section: Overall Genetic Diversitysupporting
confidence: 87%
“…In the present work, the first factor of the structuration of sorghum genetic diversity identified was the racial parameter. The results are consistence with those of Deu et al (2008), Kondombo et al (2010) and Sagnard et al (2011) respectively in Niger, Burkina-Faso and Mali on samples from world banks of genes (Deu et al, 2006).…”
Section: Population Structure and Distributionsupporting
confidence: 70%
“…Ils sont peu productifs et ont des grains de mauvaise qualité. Ces sorghos sont cultivés dans plusieurs pays comme les Etats-Unis (Ali et al, 2007 ;Murray et al, 2009 ;Wang et al, 2009), le Niger (Deu et al, 2008, la Chine (Zhang et al, 2009 ;Pei et al, 2010), la Guinée et le Mali (Sagnard et al, 2011). Le sorgho à tige sucrée est traditionnellement cultivé en Afrique où leurs tiges sont consommées comme friandises et leurs grains sont utilisés dans l'alimentation humaine et animale.…”
Section: Introductionunclassified
“…La valeur du Brix dépend des variétés et est positivement corrélée à la hauteur de la plante Zhang et al, 2009). Les variétés de sorgho à tige sucrée sont majoritairement de la race bicolor (Harlan et De Wet, 1972 ;Deu et al, 2008 ;Chantereau et al, 2010 ;Sagnard et al, 2011). Selon Pei et al (2010), les sorghos à tige sucrée ont une diversité génétique modérée.…”
Section: Introductionunclassified
“…Dentre elas, tem-se: (i) construção de mapas genéticos e mapeamento de QTLs para características quantitativas importantes -Mace and Jordan (2010) apresentam uma ampla revisão sobre esses estudos; (ii) análise do desequilíbrio de ligação (Hamblin et al, 2004(Hamblin et al, , 2007Bouchet et al, 2012;Morris et al, 2013) e mapeamento associativo (Casa et al, 2008;Sukumaran et al, 2012;Morris et al, 2013); (iii) análise da diversidade genética e do fluxo gênico entre populações (Morden et al, 1989(Morden et al, , 1990Agrama and Tuinstra, 2004;Casa et al, 2005;Folkertsma et al, 2005;Deu et al, 2006Deu et al, , 2008de Alencar Figueiredo et al, 2008;Mutegi et al, 2011;Sagnard et al, 2011;Bouchet et al, 2012); e (iv) estimação de taxas de recombinação Morris et al, 2013) e seleção Casa et al, 2006;Bouchet et al, 2012 Nos últimos anos, a descoberta de marcadores moleculares e a genotipagem de centenas de indivíduos têm sido realizadas a partir das novas plataformas de sequenciamento para muitos estudos (Varshney et al, 2009;Davey et al, 2011). Com base em um único procedimento de sequenciamento (Davey et al, 2011), essas plataformas possibilitam a geração de grandes quantidades de dados a uma velocidade bastante superior em comparação com as metodologias tradicionais (Varshney et al, 2009), mostrando eficiência, rapidez e custo reduzido.…”
Section: Marcadores Moleculares E Genotipagem Por Sequenciamentounclassified